Unplanned readmission and survival after video-assisted thoracic surgery and open thoracotomy in patients with non-small-cell lung cancer: a 12-month nationwide cohort study. (25th November 2020) - Bouabdallah, Ilies; Pauly, Vanessa; Viprey, Marie; Orleans, Veronica; Fond, Guillaume; Auquier, Pascal; D'Journo, Xavier Benoit; Boyer, Laurent; Thomas, Pascal Alexandre
Abstract: : OBJECTIVES: To compare outcomes at 12 months between video-assisted thoracic surgery (VATS) and open thoracotomy (OT) in patients with non-small-cell lung cancer (NSCLC) using real-world evidence. METHODS: We did a nationwide propensity-matched cohort study. We included all patients who had a diagnosis of NSCLC and who benefitted from lobectomy between 1 January 2015 and 31 December 2017. We divided this population into 2 groups (VATS and OT) and matched them using propensity scores based on patients' and hospitals' characteristics. Unplanned readmission, mortality, complications, length of stay and hospitalization costs within 12 months of follow-up were compared between the 2 groups. RESULTS: A total of 13 027 patients from 180 hospitals were included, split into 6231 VATS (47.8%) and 6796 OT (52.2%). After propensity score matching (5617 patients in each group), VATS was not associated with a lower risk of unplanned readmission compared with OT [20.7% vs 21.9%, hazard ratio 1.03 (0.95–1.12)] during the 12-months follow-up. Unplanned readmissions at 90 days were mainly due to pulmonary complications (particularly pleural effusion and pneumonia) and were associated with higher mortality at 12 months (13.4% vs 2.7%, P < 0.0001). CONCLUSIONS: VATS and OT were both associated with high incidence of unplanned readmissions within 12 months, requiring a better identification of prognosticators of unplanned readmissions. Our study highlights the need to improve prevention, early diagnosis and treatment of pulmonary complications in patients with VATS and OT after discharge. These findings call for improving the dissemination of systematic perioperative care pathway including efficient pulmonary physiotherapy and rehabilitation.